Konsep Percaya Diri Dalam Al Qur’an Dan Implikasinya Terhadap Kehidupan Manusia - Suhaili, Achmad (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2019)
Self-confidence is an aspect of the human personality that functions important to actualize its potential. Without self-confidence, many problems will arise in humans. With the presence of confidence, someone will get along easily. Facing people who are older, smarter and richer, they are not ashamed to be awkward. They will dare to show themselves as they are, without prominently-highlighting excesses and covering up shortcomings. This is because people who are confident have truly understood and trusted their condition, so that they have been able to accept their condition as they are. Does the Qur'an talk about the concept of self-confidence? And how does the Qur'an talk about the concept of self-confidence? Of course there is no verse of the Qur'an that speaks of self-confidence lexically